Voltage regulator design for synchronous generators - Ng, Bing Rong. (2009)
A synchronous generator requires a prime mover to drive it up to synchronous speed for it to be able to generate electrical power. The terminal output voltage from the generator is controllable through the utilization of a voltage regulator. The speed control of the generator is achieved using a separate circuit called a speed governor. The governor works closely with the voltage regulator circuit. For a synchronous generator to synchronize to the electrical grid, three conditions have to be met. They are the phase angle, generated voltage and frequency. The voltage regulator designed for this project aims to replace the manual control with an automated controlled by interfacing the controller with a microprocessor, AGC. The automatic voltage regulator will then regulate the generator’s terminal voltage by controlling the excitation current in the field windings of the generator. This automation will allow the generator to supply power in an isolated mode with or with the generator synchronized with the main electrical grid. Knowledge from electronics are a key advantage in the design of this project and control theory is also used to understand the automation of the AVR.